Implementation of postnatal care for HIV-positive mothers in the Free State: Nurses' perspectives - Lumka Mangoejane; Mokholelana M. Ramukumba (AOSIS, 2019)
Background: Postnatal care (PNC) provides the opportunity for protecting the lives of women infected with human immune deficiency virus (HIV) and their babies. The prevention of mother-to-child transmission of HIV (PMTCT) guidelines provide a framework for implementation of PNC. There has been no empirical evidence on how the nurses at the clinic level implement these guidelines. In addition, there are reports that PNC has been neglected in South Africa. Aim: The study aimed to explore the implementation of PNC for HIV-positive women, by explicating nurses' views regarding their practices. Setting: The study was conducted in 2015 at three clinics at Mangaung Metro Municipality in the Free State. Methods: A qualitative, evaluative case study was conducted to provide a detailed account of the implementation of PNC, using 2015 PMTCT guidelines as a framework for evaluation. Eighteen key informants participated in three focus groups. Data were reviewed through direct thematic analysis. Results: Four themes emerged from data analysis, namely, guidelines as an empowering tool, implementation of HIV guidelines, perceived successes and challenges of postnatal HIV care, and measures to strengthen postnatal HIV care services. The study found that nurses interpreted and used guidelines to direct their practice. However, there were challenges and some successes. Conclusion: It was concluded that nurses had a good understanding of the guidelines provided for their practices and implemented them with various levels of success. Effective management of HIV-infected women during the postnatal period requires well-designed multidisciplinary collaborations, adequate resources, continuous professional development programmes, a high level of competence and confidence.